Tradisi Batuyang: Eksistensi Nilai Islam Pada Produk Budaya Masyarakat Dayak Bakumpai Kalimantan Tengah: Batuyang Tradition: Islamic Values in Dayak Bakumpai Culture of Central Kalimantan - Supriadi, Akhmad; Abdullah, Muhammadkhair; Faridatunnisa, Nor; Saiful Khair, Muhammad; Khalfiah, Yuliani; Alawiyah, Tuti (Direktorat Jenderal Bimbingan Masyarakat Islam, 2024)
Islam and culture are two variables that cannot be separated. The interaction between the two results in acculturation or Islamization of local culture. This means that things that are substantial in a culture will be inserted with Islamic values, so that the animism-dynamism nuances in a local tradition will fade. One example of a culture that has undergone Islamization in Indonesia is the batuyang tradition. This research aims to find out the process of implementing the batuyang tradition by the Dayak Bakumpai community, Central Kalimantan. The main approach used in this research is Edmund Husserl's phenomenology, and data collection is carried out through observation, documentation, and interviews carried out from April to October 2022 on several samples selected by applying the purposive sampling method. The data obtained were analyzed using the descriptive-analytical method, with Ahmad Rafiq's Qur'anic reception theory as the basis for analysis. The results showed that there are Islamic values in the batuyang tradition. This is indicated by the recitation of salawat during the event and the recitation of fatihah ampat and congratulatory prayers at the end of the event. This procession reflects the flexibility of Islamic teachings in human life and its important role in the transformation of local culture.